Penerapan Kombinasi Terapi Murotal Al-Qur’an Dengan Relaksasi Napas Dalam Pada Nyeri Kateter Urin di IGD - Halim Betta Sugiri; Hermawati Hermawati; Waluyo Waluyo (Inovasi Kesehatan Global, 2025)
Background: Urinary catheter insertion is an invasive medical procedure that often causes pain due to friction between the catheter and the urethra. This pain can lead to discomfort and stress for the patient. Based on initial observations in the Emergency Department (ED) over a period of three days, it was found that all patients undergoing urinary catheter insertion complained of pain. As an alternative pain management approach, one non-pharmacological method that can be used is a combination of Quranic murotal therapy and deep breathing relaxation techniques. This therapy is chosen because it is believed to have a calming effect and can reduce the perception of pain without the need for medication. Objective: This study aims to determine the difference in pain levels before and after the application of the combination of Quranic murotal therapy with deep breathing relaxation techniques during urinary catheter insertion in the ED. Method: This research uses a descriptive case study design involving two respondents. Both patients received an intervention consisting of Quranic murotal therapy played during the procedure, accompanied by instructions to practice deep breathing relaxation techniques. The therapy was applied during the urinary catheter insertion to assess changes in pain levels experienced by the patients. Results: The results showed that the pain level of the first respondent decreased from moderate pain to mild pain after the intervention. The second respondent experienced a reduction in pain from severe to moderate after the combined therapy was applied. Both respondents reported improved comfort after the therapy. Conclusion: The combination of Quranic murotal therapy with deep breathing relaxation techniques was proven effective in reducing pain levels in patients undergoing urinary catheter insertion in the ED. This therapy can serve as a beneficial non-pharmacological alternative for reducing pain during invasive medical procedures.